Digital Toolkit for the Representation, Survey, Preservation and Enhancement of 20th Century Buildings in Brazil and India - Luca Rossato (Proceedings, 2017)
The contribution deals with the elaboration of a digital methodology to be applied on 20th century buildings in Brazil and India as toolkit for their conservation and enhancement. The research has gone through a careful planning and guided process able to integrate all information related to the geometry with details concerning materials, phases of realization, technical characteristics, and environmental. The undertaken research path has shown that the application of technologies used through appropriate methodologies can be an effective approach for the preservation and enhancement of 20th century architectures in “global south countries” and for the transmission of this heritage to future generations all over the world.